Creep and Recovery Behaviour of Polyolefin-Rubber Nanocomposites Developed for Additive Manufacturing - Daver, Fugen; Kajtaz, Mladenko; Brandt, Milan; Shanks, Robert (Polymers, 2016)
Nanocomposite application in automotive engineering materials is subject to continual stress fields together with recovery periods, under extremes of temperature variations. The aim is to prepare and characterize polyolefin-rubber nanocomposites developed for additive manufacturing in terms of their time-dependent deformation behaviour as revealed in creep-recovery experiments. The composites consisted of linear low density polyethylene and functionalized rubber particles. Maleic anhydride compatibilizer grafted to polyethylene was used to enhance adhesion between the polyethylene and rubber; and multi-walled carbon nanotubes were introduced to impart electrical conductivity. Various compositions of nanocomposites were tested under constant stress in creep and recovery. A four-element mechanistic Burger model was employed to model the creep phase of the composites, while a Weibull distribution function was employed to model the recovery phase of the composites. Finite element analysis using Abaqus enabled numerical modelling of the creep phase of the composites. Both analytical and numerical solutions were found to be consistent with the experimental results. Creep and recovery were dependent on: (i) composite composition; (ii) compatibilizers content; (iii) carbon nanotubes that formed a percolation network.